PENGGUNAAN MODEL PEMBELAJARAN INKUIRI UNTUK MENDORONG KEAKTIFAN SISWA DALAM PROSES BELAJAR - Yang Gusti Feriyanti; Paramina Indra Yani; Muhammad Arsyad (Ahsani Taqwim: Jurnal Pendidikan dan Keguruan, 2025)
Using the inquiry learning model to increase student activity in the learning process. The inquiry method encourages students to question, investigate, and make their own discoveries, thereby increasing their understanding and involvement in learning. The use of the inquiry model significantly increases student activity, promotes critical thinking, and deepens their understanding of the subject matter. The pedagogical implications of this research support the use of the inquiry model as an effective strategy to facilitate more student-centered and discovery-oriented learning. The aim of using the inquiry learning model is to increase student activity in the learning process through student-centered learning, facilitating exploration, inquiry and problem solving. By encouraging students to question, investigate, and make their own discoveries, the inquiry model helps build deeper understanding, increases student engagement, and promotes the development of critical thinking skills and research skills that are important in learning. The inquiry learning model promotes student activity through an approach that places students as the main learning agents. In inquiry, students are invited to ask questions, investigate and discover their own knowledge through exploration and reflex. The purpose of this writing is to discuss strategies for implementing inquiry learning. The inquiry learning strategy states that the teacher as a learning source is not the only one, there are many more learning sources that can support successful learning. The teacher is only a facilitator, a guide who always directs students in learning. Students are designed as discoverers or seekers of knowledge, a teacher's job is to manage students so that they gain knowledge and become meaningful.